2011
DOI: 10.1590/s0100-69162011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinization and maize and cowpea yield in the crop rotation system using saline waters

Abstract: ABSTRACT:The use of saline water and the reuse of drainage water for irrigation depend on longterm strategies that ensure the sustainability of socio-economic and environmental impacts of agricultural systems. In this study, it was evaluated the effects of irrigation with saline water in the dry season and fresh water in the rainy season on the soil salt accumulation yield of maize and cowpea, in a crop rotation system. The experiment was conducted in the field, using a randomized complete block design, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 24 publications
1
21
1
22
Order By: Relevance
“…During the sunflower cultivation the monthly rainfalls were 30.4, 86.8, 15.6 and0mm for March, April, May andJune, respectively. Contrary to this, BEZERRA et al (2010) andLACERDA et al (2011) did not observe residual effects of salinity on crops of cowpea and maize in crop rotation systems, after the areas had been irrigated with water of EC up to 5.0dS m -1 during the dry season. However, the total rainfall during these studies was at least three times higher than that observed in the present study.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…During the sunflower cultivation the monthly rainfalls were 30.4, 86.8, 15.6 and0mm for March, April, May andJune, respectively. Contrary to this, BEZERRA et al (2010) andLACERDA et al (2011) did not observe residual effects of salinity on crops of cowpea and maize in crop rotation systems, after the areas had been irrigated with water of EC up to 5.0dS m -1 during the dry season. However, the total rainfall during these studies was at least three times higher than that observed in the present study.…”
Section: Resultsmentioning
confidence: 79%
“…In cowpea, for example, the application of water with an EC of 5.0dS m -1 throughout the cycle and during germination and initial growth stage caused significant reductions in the number of pods and seed yield per plant. However, irrigation of the crop with the same water during flowering and pod formation stages did not affect the growth and crop yield, and allowed the replacement of about 40% of good quality water (LACERDA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As concentrações de sais que restringem o crescimento do feijão-caupi variam entre os cultivares e parecem depender da composição iônica do meio, das concentrações de íons potencialmente tóxicos, particularmente Na + e Cl -, que proporcionam redução no crescimento foliar e na assimilação líquida de carbono, repercutindo negativamente na produtividade da cultura (NEVES et al, 2009;LACERDA et al, 2011). O excesso de sais pode comprometer as funções fisiológicas e bioquímicas das plantas, causando estresse osmótico, o que resulta em distúrbios das relações hídricas, alterações na absorção e utilização de nutrientes essenciais além do acúmulo de íons tóxicos (ASSIS JÚNIOR et al, 2007;CALVET et al, 2013).…”
Section: Introductionunclassified
“…CE 1,2 -condutividade elétrica de 1,2 dS m -1 , CE 3,3 -condutividade elétrica de 3,3 dS m -1 , ECP -massa de espiga com palhas, ESP -massa de espiga sem palhas, PPH -produtividade de polpa hidratada, PPD -produtividade de polpa desidratada, D -diâmetro do caule, AIE -altura de inserção de espigas, A -altura de plantas, MFPA -matéria fresca da par te aérea e MSPA -matéria seca da par te aérea Lacerda et al (2011).…”
Section: Resultsunclassified